DANGER OF ALCOHOL FOR PATIENTS WITH ARTERIAL HYPERTENSION DURING ANTIHYPERTENSIVE THERAPY - M. P. Savenkov; M. K. Danilova; S. N. Ivanov; A. M. Savenkova; S. V. Ivanova (Рациональная фармакотерапия в кардиологии)
Aim. To develop a test on tolerability of small alcohol doses (SAD), to study hemodynamic and vestibular changes induced by SAD during mono- and combined antihypertensive therapy.Material and methods. 30 healthy volunteers and 292 patients with arterial hypertension 1-2 stages were involved in the study. Tolerance to SAD was estimated in untreated hypertensive patients (n=77), patients receiving one (n=218), two (n=46) and three (n=28) antihypertensive drugs. Tolerance to SAD was evaluated by blood pressure changes as well as change of upright body balance and subjective sensations of the patient.Results. Hypotension and circulatory vestibular disorders can be induced by alcohol consumption during antihypertensive therapy. These disorders appear more often due to peripheral vasodilators as well as combined antihypertensive therapy.Conclusion. It is necessary to inform the patient about risk of alcohol taking and necessity to restrict of its dose during antihypertensive therapy.